AKSES DAN DAMPAK PENYALURAN DANA BERGULIR LPDB KEMENTERIAN KUMKM PADA KOPERASI DI KOTA TANGERANG SELATAN - Dewi Rohma Wati (Jurnal Bisnis Tani, 2018)
Micro, small and medium enterprises (MSMEs) are drivers of the country's economy that can absorb labor and improve the quality of the people's economy. However, the development of MSMEs typically linked to the role of financial institutions that provide capital, namely cooperatives. The objectives of this study are: (1) to identify the characteristics of financial institutions incorporated as cooperatives in South Tangerang City; (2) analyze the accessibility of cooperatives in financing Revolving Fund Management Institution (LPDB) in South Tangerang City; (3) analyze the impact of LPDB financing on lending to MSMEs in South Tangerang City. The analytical method used to answer the first objective is qualitative descriptive, and the Heckman Selection Model to answer the second and third goals. The results of the study showed that consumer cooperatives, namely 69.5% dominated cooperatives in South Tangerang City. Cooperatives can access revolving funds from LPDB KUMKM in South Tangerang City, but only three cooperatives have succeeded in becoming partners of LPDB KUMKM. The factors that had influence are the length of time the cooperative established, the distance of cooperatives to LPDB offices, the amount of revolving funds distributed, and the amount capital owned by the cooperative itself. Revolving funds from LPDB KUMKM have a positive impact on increasing cooperative business which showed in the value of assets and the remaining results of the business. The impact on the remaining business profit is affected by the number of cooperative members, cooperative capital, and cooperative capital.